Nerve Growth Factor Biodelivery: A Limiting Step in Moving Toward Extensive Clinical Application? - Alastra, Giuseppe; Aloe, Luigi; Baldassarro, Vito Antonio; Calzà, Laura; Cescatti, Maura; Duskey, Jason Thomas; Focarete, Maria Letizia; Giacomini, Daria; Giardino, Luciana; Giraldi, Valentina; Lorenzini, Luca; Moretti, Marzia; et al. (Frontiers in Neuroscience, 2021)
Nerve Growth Factor (NGF) was the first-discovered member of the neurotrophin family, a class of bioactive molecules which exerts powerful biological effects on the CNS and other peripheral tissues, not only during development, but also during adulthood. While these molecules have long been regarded as potential drugs to combat acute and chronic neurodegenerative processes, as evidenced by the extensive data on their neuroprotective properties, their clinical application has been hindered by their unexpected side effects, as well as by difficulties in defining appropriate dosing and administration strategies. This paper reviews aspects related to the endogenous production of NGF in healthy and pathological conditions, along with conventional and biomaterial-assisted delivery strategies, in an attempt to clarify the impediments to the clinical application of this powerful molecule.